Finding the Balance: European Military Power in Early Modern Asia. Issue 3 (March 2015) - Clulow, Adam
Abstract: This article assesses recent developments in the debate over European military superiority in early modern Asia. It does so by focusing on Tonio Andrade's groundbreaking 2011 study, Lost Colony: The Untold Story of China's First Great Victory over the West, which stakes out a valuable middle ground between two clashing positions by suggesting that while Europeans did possess a genuine technological advantage it was not nearly as expansive as is sometimes assumed by supporters of the military revolution thesis. The goal of this article is to summarize Andrade's findings and to consider whether his limited advantage template can be applied to East Asia's second great military power, Tokugawa Japan.